HOSPITALITY STUDENTS’ NEED ANALYSIS TO LEARN ENGLISH AT MAKASSAR TOURISM POLYTECHNIC - Muhammad Chairul Aris; Noer Jihad Saleh; Nasmilah Nasmilah (International Journal of Social Science, 2022)
This study aims to find out hospitality department students’ need to learn English at Makassar Tourism Polytechnic and design the syllabus after the assessment. The study consists of 40 students as its population. The study used mixed methods, which were quantitative and qualitative, by giving questionnaires to students and semi-interviews to students and lecturers to support their answers. The result showed that the students need English materials that support their communicative competence. So the syllabus was designed by prioritizing speaking as the main course in order to be able to communicate with the guests from foreign countries. Not only that, but it also prepares students to get jobs in hospitality industries. The syllabus designed as the output of this study, which covers hospitality-related topics, grammar items, and a variety of learning activities that engage with students’ interest in the class.